The Role of TDP-43 in Military-Relevant TBI and Chronic Neurodegeneration - Heyburn, Lanier; Sajja, Venkata S. S. S.; Long, Joseph B. (Frontiers in Neurology, 2019)
Due largely to the use of improvised explosive devices (IEDs) and other explosives in recent military conflicts, blast-related TBI has emerged as a prominent injury sustained by warfighters. In the recent wars in Iraq and Afghanistan, traumatic brain injury (TBI) has been one of the most common types of injury sustained by soldiers and military personnel; of the ~380,000 TBIs reported in service members from 2000-2017, 82.3% were classified as mild (mTBI). While mTBI is associated with normal structural imaging, brief or no loss of consciousness, and rapid recovery of mental state, mTBI can nevertheless lead to persistent behavioral and cognitive effects. As in other cases of mTBI, exposure to low-level blast often does not cause immediate overt neurological effects, but may similarly lead to persistent behavioral and cognitive deficits. These effects are likely to be compounded when multiple exposures to blast and/or impact are sustained, since there is increasing evidence that multiple mTBIs can lead to chronic neurodegeneration. One common form of this deleterious outcome is frontotemporal lobar degeneration (FTLD), which is a progressive neurodegenerative process marked by atrophy of the frontal and temporal lobes, leading to frontotemporal dementia, a common form of dementia affecting behavior, cognition and language. About half of all cases of FTLD are marked by TAR-DNA binding protein (TDP-43)-positive protein inclusions. TDP-43, a DNA/RNA binding protein, controls the expression of thousands of genes and is associated with several neurodegenerative diseases including amyotrophic lateral sclerosis, Alzheimer’s disease, Huntington’s disease, and chronic traumatic encephalopathy. TDP-43 abnormalities have also been associated with traumatic brain injury in both pre-clinical and clinical studies. The role of TDP-43 in the manifestation of FTLD pathology in military TBI cases is currently unclear, and to date there has been only a limited number of pre-clinical studies addressing the effects of repeated blast-related mild TBI (rbTBI) in relation to FTLD and TDP-43. This review will summarize some of these findings and address the concerns and critical knowledge gaps associated with FTLD manifestation with military populations, as well as clinical findings on other forms of mTBI.